2018
DOI: 10.33899/mmed.2018.159185
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of transient tachypnea of newborns

Abstract: Background: Transient tachypnea of the newborn (TTN) is a frequently encountered form of neonatal respiratory distress. The underlying mechanism involves residual lung fluid that is delayed in clearance. TTN primarily occurs soon after birth and can last from 24 to 72 hours. Risk factors for TTN include elective cesarean section, male sex, late prematurity, low birth weight, macrosomia, polycythemia, maternal asthma and maternal diabetes. Treatment is often supportive with observation and potential oxygen supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
4
0
0
Order By: Relevance
“…This is in agreement with the results of other studies [26,27]. It was also observed that full term was significantly higher in TTN, which is consistent with other results [6,26]. Birth asphyxia constituted 35(14%) of the total respiratory distress cases in our study.…”
Section: Respiratory Distress and Its Outcome Among Neonates Admitted...supporting
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with the results of other studies [26,27]. It was also observed that full term was significantly higher in TTN, which is consistent with other results [6,26]. Birth asphyxia constituted 35(14%) of the total respiratory distress cases in our study.…”
Section: Respiratory Distress and Its Outcome Among Neonates Admitted...supporting
confidence: 94%
“…In the current study, it was observed that male gender was significantly higher in TTN (59.6% versus 40.4% for female, p=0.03). This is in agreement with the results of other studies [26,27]. It was also observed that full term was significantly higher in TTN, which is consistent with other results [6,26].…”
Section: Respiratory Distress and Its Outcome Among Neonates Admitted...supporting
confidence: 93%
See 2 more Smart Citations